Brain‐derived neurotrophic factor Val66Met polymorphism and cognitive function in persons with cardiovascular disease. Issue 4 (28th October 2013) - Szabo, Ashley J.; Alosco, Michael L.; Miller, Lindsay A.; McGeary, John E.; Poppas, Athena; Cohen, Ronald A.; Gunstad, John
Abstract Aim Cognitive impairment is common among persons with cardiovascular disease (CVD), and several potential aetiological mechanisms have been described, including contributions of genetic markers such as variations in the brain‐derived neurotrophic (BDNF) gene. This current study examined the associations of BDNF genotype with cognitive function among individuals with CVD. Methods This study included 110 participants with CVD who completed a comprehensive neuropsychological battery that assessed global cognitive function, attention/executive function, memory, language, and visuospatial abilities. All participants also underwent blood draw to provide a DNA sample that was used to determine BDNF genotype. Carriers of either one or two copies of the methionine allele of BDNF were categorized into one group (n = 33); non‐carriers were categorized into a second group (n = 77). Results After adjustment for demographic and medical characteristics, hierarchical regression analyses revealed persons with one or more methionine alleles displayed better performance than valine/valine individuals for attention/executive function (β = 0.22, P = 0.047) and memory (β = 0.25, P = 0.03), as well as a trend for language (β = 0.19, P = 0.08) and visuospatial abilities (β = 0.21, P = 0.06). Conclusions BDNF Val66Met had little impact on cognitive functioning in a sample of older adults with CVD, and significant findings contradicted that predicted by past work. Future work is much needed to clarify the mechanisms of these findings, particularly studies examining both circulating BDNF levels and genetic variation in the BDNF gene and cognitive function over time.